Expandable polystyrene-based resin particle for cushioning material padding

JP2023146799A5Active Publication Date: 2025-01-21JSP CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022054184
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-29
Publication Date
2025-01-21
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

Expandable polystyrene resin particles for cushion stuffing face issues with adhesion to hoppers in high humidity, blocking during expansion, poor fluidity, and electrostatic charging, leading to poor touch and fit in cushioning materials.

Method used

The use of polystyrene resin particles coated with a mixture of stearic acid metal salts, stearamide, and antistatic agents, with specific ratios and amounts, to enhance fluidity, anti-blocking properties, and antistatic performance, using butane, pentane, and cyclohexane as foaming agents.

Benefits of technology

The solution provides polystyrene resin particles with improved fluidity, reduced blocking, and antistatic properties, resulting in cushioning materials with enhanced touch and fit.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide an expandable polystyrene-based resin particle for cushioning material padding, having excellent flowability and anti-blocking property as the expandable polystyrene-based resin particle, and excellent flowability and anti-static property of an expandable particle produced using the expandable polystyrene-based resin particle, and capable of providing a cushioning material excellent in touch feeling as the final product.SOLUTION: An expandable polystyrene-based resin particle for cushioning material padding is composed of a resin particle body having a polystyrene-based resin as the base resin, a foaming agent contained in the resin particle body, and a coating material coating the resin particle body. An average particle diameter of the resin particle body is 0.3 mm or more and 0.5 mm or less, and the coating material contains metal stearate A, stearic acid amide and an anti-static agent. The metal stearate A comprises 40 mass% or more and 100 mass% or less of magnesium stearate, and 0 mass% or more and 60 mass% or less of zinc stearate (the total of both is 100 mass%). Based on 100 pts.mass of the resin particle body, a coating amount of the metal stearate A is 0.1 pt.mass or more and less than 0.4 pt.mass, a coating amount of the stearic acid amide is 0.01 pt.mass or more and 0.5 pt.mass or less, and a coating amount of the anti-static agent is 0.2 pt.mass or more and 0.8 pt.mass or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to expandable polystyrene resin particles for use as cushioning material fillers. [Background technology]

[0002] Conventionally, cushioning materials with cushioning properties have been known, in which foamed particles such as polystyrene foamed particles are filled inside a cloth or other bag-like body. Such cushioning materials are used as cushions, sofas, mattresses, etc. For example, Patent Document 1 discloses foamed resin particles for filling cushioning materials, which consist of foamed resin particles with an average particle diameter of 400 to 900 μm and a flow promoter such as zinc stearate. The above-mentioned foamed resin particles for filling cushioning materials are specified to contain 0.4 to 1.5 parts by weight of the flow promoter per 100 parts by weight of the foamed resin particles, and it is explained that this can suppress the abnormal noise generated when the foamed resin particles filled in the cushioning material rub against each other as they flow.

[0003] Furthermore, Patent Document 2 proposes foamable polystyrene resin particles for use as filling material for bead cushions. The above foamable polystyrene resin particles are specified to contain magnesium stearate, fatty acid monoglycerides, and hydroxyalkylamines in a predetermined range on the particle surface per 100 parts by weight of the base resin. Patent Document 2 explains that the above foamable polystyrene resin particles exhibit less blocking during foaming when manufacturing the foamed particles, and that the manufactured foamed particles have good antistatic properties and are less prone to deterioration of fluidity due to moisture absorption. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] WO2003 / 032783 publication [Patent Document 2] Japanese Patent Publication No. 2021-155517 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] Expandable polystyrene resin particles for cushioning material fillings have unique challenges that differ from those of expandable polystyrene resin particles for in-mold molding. For example, because the particle size of foamed polystyrene resin particles used for cushioning material filling is smaller than that of foamed particles used for in-mold molding, problems such as foamed polystyrene resin particles adhering to and remaining in the corners of hoppers, etc., in high-temperature and high-humidity environments, and problems such as particles sticking together and blocking occurring when foaming the foamed polystyrene resin particles tend to occur more frequently than with foamed polystyrene resin particles used for in-mold molding. When foamed particles are filled into bags in a blocked state to manufacture cushioning material, there is a problem that the feel and fit of the cushioning material will be poor.

[0006] Furthermore, if the foam particles were significantly charged, a large amount of foam particles would cling to the filling port of the filling machine and the outer surface of the bag when filling the bag using a filling machine, making the filling process difficult. In addition, when using the cushioning material, the foam particles inside could rub against each other and become charged, potentially causing the cushioning material to attract dust and other particles. Moreover, if the fluidity of the foam particles was poor, the feel and fit of the cushioning material would be negatively affected.

[0007] According to the inventors' research, foamed polystyrene resin particles or foamed particles using the same, which contain an antistatic agent to a sufficient degree to adequately improve the electrostatic properties of foamed particles used as fillings for cushioning materials and which also sufficiently suppress blocking, tend to have insufficient fluidity. In other words, it has been difficult with conventional technology to provide foamed polystyrene resin particles or foamed particles that exhibit good antistatic properties, anti-blocking properties, and fluidity.

[0008] In other words, Patent Document 1 makes no mention of the flowability and blocking issues related to foamed polystyrene resin particles for manufacturing foamed particles, and there was room for improvement regarding the flowability of the foamed particles. In particular, Patent Document 1 did not consider foamed particles that exhibit high flowability while also providing an antistatic effect. Furthermore, while Patent Document 2 examines the blocking problem during the foaming process, as well as the fluidity and antistatic properties of the foamed particles, there was still room for further investigation into how to improve all of these properties—blocking, fluidity, and antistatic properties—in a balanced manner.

[0009] The present invention has been made in view of the above background, and provides foamed polystyrene resin particles for cushioning material fillings that have good fluidity and antiblocking properties as foamed polystyrene resin particles, as well as good fluidity and antistatic properties of foamed particles manufactured using said foamed polystyrene resin particles, and that can provide a cushioning material with an excellent feel as a final product. [Means for solving the problem]

[0010] The foamable polystyrene resin particles for cushioning material filling of the present invention are foamable polystyrene resin particles for cushioning material filling, comprising a resin particle body with a polystyrene resin as the base resin, a foaming agent contained in the resin particle body, and a coating agent covering the resin particle body, wherein the average particle diameter of the resin particle body is 0.3 mm or more and 0.5 mm or less, the coating agent comprises metal stearate salt A, stearate amide, and an antistatic agent, the metal stearate salt A consists of 40% by mass or more and 100% by mass of magnesium stearate and 0% by mass or more and 60% by mass of zinc stearate (provided that the sum of both is 100% by mass), and the amount of coating of metal stearate salt A per 100 parts by mass of the resin particle body is 0.1 parts by mass or more and less than 0.4 parts by mass, the amount of coating of stearate amide is 0.01 parts by mass or more and 0.5 parts by mass or less, and the amount of coating of antistatic agent is 0.2 parts by mass or more and 0.8 parts by mass or less. [Effects of the Invention]

[0011] The foamed polystyrene resin particles for cushioning material fillings of the present invention have good fluidity and anti-blocking properties, and are easy to handle when used in the manufacture of foamed particles. Furthermore, the foamed polystyrene resin particles for cushioning material fillings of the present invention contribute to providing foamed particles that have good fluidity and antistatic properties, and enable the provision of a cushioning material with an excellent tactile feel as a final product. [Modes for carrying out the invention]

[0012] As a result of diligent research into the above-mentioned problems, the present inventors have found that by using a coating agent that coats the resin particle body in combination with metal stearate A and stearate amide as flow promoters, it is possible to improve the blocking prevention and fluidity of foamed polystyrene resin particles in a balanced manner, and further improve the antistatic properties and fluidity of foamed particles obtained by foaming the foamed polystyrene resin particles in a balanced manner, thus completing the present invention.

[0013] In other words, the foamable polystyrene resin particles for cushioning material filling of the present invention are composed of a resin particle body with a polystyrene resin as the base resin, a foaming agent contained in the resin particle body, and a coating agent covering the resin particle body. In the present invention, the average particle diameter of the resin particle body is 0.3 mm or more and 0.5 mm or less, and the coating agent includes metal stearate A, stearate amide, and an antistatic agent. The above-mentioned metal stearate salt A is composed of 40% to 100% by mass of magnesium stearate and 0% to 60% by mass of zinc stearate. In metal stearate salt A, the total amount of magnesium stearate and zinc stearate is 100% by mass. The coating amount of the metal stearate A is 0.1 parts by mass or more and less than 0.4 parts by mass, the coating amount of the stearic acid amide is 0.01 parts by mass or more and 0.5 parts by mass or less, and the coating amount of the antistatic agent is 0.2 parts by mass or more and 0.8 parts by mass or less, with respect to 100 parts by mass of the resin particle body.

[0014] In the following description, the foamed polystyrene-based resin particles for the cushioning material stuffing of the present invention may be simply referred to as the foamed resin particles of the present invention, and the polystyrene-based resin foamed particles produced using the foamed resin particles of the present invention may be simply referred to as foamed particles. Also, regarding the present invention, a configuration such as a cushion, sofa, mattress, pillow, stuffed toy, etc., which has cushioning properties by enclosing foamed particles in a bag body made of cloth or the like, is collectively referred to as a cushioning material. The cushioning material includes a bag body made of cloth or the like and the foamed particles filled inside the bag body. The shape of the bag body is not particularly limited, and examples of the material include a woven or knitted fabric, non-woven fabric, sheet made of resin or the like, leather, artificial leather, etc., having a weight such that the foamed particles filled inside do not come out.

[0015] The foamed resin particles of the present invention having the above-described configuration have good fluidity and sufficient blocking prevention. Further, the foamed particles produced using the resin particles of the present invention are excellent in antistatic properties and fluidity, so that when filling the cushioning material, it is possible to prevent the foamed particles from adhering to the filling machine or the outer surface of the bag body, and it is possible to provide a cushioning material with a good touch. In other words, the foamed resin particles of the present invention contribute to providing foamed particles having the above-described desirable effects. The foamed resin particles of the present invention will be described in more detail below.

[0016] [Resin particle body] The resin particle body in the present invention is composed of a polystyrene-based resin as a base resin. Here, the fact that the polystyrene-based resin is the base resin means that the resin particle body is generally composed of a polystyrene-based resin and may optionally contain other resins or materials. Any materials will be described later.

[0017] In the present invention, the polystyrene-based resin means a resin containing 50% by mass or more of structural units derived from styrene. Examples of the polystyrene-based resin include polystyrene (general-purpose polystyrene: GPPS), styrene-methacrylic acid copolymer, styrene-methacrylic acid-methyl methacrylate copolymer, styrene-acrylic acid copolymer, styrene-maleic anhydride copolymer, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, styrene-acrylonitrile copolymer, high-impact polystyrene (HIPS) containing a rubber component such as butadiene rubber or styrene-butadiene rubber, etc. Further, the polystyrene-based resin may contain structural units derived from a branching agent such as divinylbenzene or a polyfunctional macromonomer. Among these, it is particularly preferable to use polystyrene as the polystyrene-based resin.

[0018] (Average particle diameter) The average particle diameter of the resin particle body in the present invention is 0.3 mm or more and 0.5 mm or less. If it is less than 0.3 mm, production may be difficult in some cases, and if it exceeds 0.5 mm, the touch feeling of the cushioning material composed of using the foamed particles produced therefrom as a stuffing material may deteriorate in some cases. Incidentally, regarding the present invention, the average particle diameter of the resin particle body is the cumulative 63% diameter (that is, d63) calculated based on the particle size distribution on a volume basis. A particle size distribution measuring device is used for the measurement of the above average particle diameter.

[0019] [Blowing agent] A blowing agent is contained in the resin particle body in the present invention. The above-mentioned foaming agent is appropriately selected from foaming agents used to produce polystyrene resin foam particles. In particular, it is preferable that the foaming agent contains one or more selected from butane, pentane, and cyclohexane, more preferably both butane and pentane, and even more preferably all of butane, pentane, and cyclohexane. By selecting such a foaming agent, the amount of residual styrene monomer in the foamed resin particles can be kept at an appropriate level, and the amount of residual styrene monomer and volatile organic compounds emitted from the foamed particles produced using the foamed resin particles can be kept at an appropriate level. Therefore, when a cushioning material is constructed using such foamed particles, the generation of unpleasant odors during use can be prevented. In the following, residual styrene monomer may be referred to as R-SM and volatile organic compounds as VOC.

[0020] In particular, the foaming agent contains all of the above-mentioned butane, pentane, and cyclohexane, and the total content of butane, pentane, and cyclohexane in the foamed polystyrene resin particles is 4% by mass or more and 8% by mass or less per 100% by mass of the foamed resin particles, and the mass ratio of the total of butane and pentane to cyclohexane is 1:0.1 to 1:0.5. As described above, foamed resin particles containing butane, pentane, and cyclohexane in predetermined ranges as foaming agents not only suppress the odor of the final cushioning material product, but also significantly improve the blocking and foaming properties of the foamed resin particles, and contribute to providing foamed particles that are resistant to deformation.

[0021] The butane mentioned above may include n-butane, isobutane, or a mixture thereof. The butane is a gas at 25°C and 1 atm, with a boiling point of approximately -11°C. The pentane mentioned above may be n-pentane, isopentane, or a mixture thereof. The pentane is a liquid at 25°C and 1 atm, and its boiling point is approximately 35°C. The above-mentioned cyclohexane is a cyclic aliphatic hydrocarbon, is liquid at 25°C and 1 atm, and has a boiling point of approximately 81°C.

[0022] [Coating agent] The foamed resin particles of the present invention consist of a resin particle body containing a foaming agent and a coating agent that covers the resin particle body. The above coating agent includes metal stearate A, stearate amide, and an antistatic agent.

[0023] (Metal stearate A) The metal stearate A is preferably applied in an amount of 0.1 parts by mass or more and less than 0.4 parts by mass per 100 parts by mass of the resin particle body, and more preferably in an amount of 0.2 parts by mass or more and 0.4 parts by mass or less.

[0024] In the present invention, metal stearate salt A is composed of 40% to 100% by mass of magnesium stearate and 0% to 60% by mass of zinc stearate. However, the total of both is 100% by mass. If the magnesium stearate content is less than 40% by mass in 100% by mass of metal stearate salt A, the fluidity and blocking properties of the foamed resin particles may not be adequately improved. From the viewpoint of achieving better fluidity of foamed resin particles, it is preferable that the metal stearate salt A consists of 60% to 80% by mass of magnesium stearate and 20% to 40% by mass of zinc stearate (provided that the total of both is 100% by mass).

[0025] From the viewpoint of more fully exhibiting the effect of coating with metal stearate salt A, it is preferable that the amount of magnesium stearate coating is 0.1 parts by mass or more and less than 0.4 parts by mass, and the amount of zinc stearate coating is less than 0.2 parts by mass (however, including 0 parts by mass) per 100 parts by mass of the resin particle body, and it is more preferable that the amount of magnesium stearate coating is 0.13 parts by mass or more and less than 0.35 parts by mass, and the amount of zinc stearate coating is less than 0.17 parts by mass (however, including 0 parts by mass) per 100 parts by mass of the resin particle body.

[0026] (Amide stearate) The amount of stearate amide coating per 100 parts by mass of resin particles is 0.01 parts by mass or more and 0.5 parts by mass or less, and more preferably 0.03 parts by mass or more and 0.3 parts by mass or less. In this invention, the resin particle body is coated with stearate amide in combination with metal stearate salt A. When metal stearate salt A is included as the coating agent but stearate amide is not, desirable fluidity and blocking properties are difficult to achieve. Our investigations have shown that using stearate amide as a coating agent can significantly improve the fluidity of foamed resin particles, but it tends to promote the occurrence of blocking during foaming. However, by using metal stearate salt A and stearate amide in combination as coating agents, blocking is effectively suppressed while the fluidity of foamed resin particles tends to be further improved.

[0027] In the present invention, the coating agent can have a mass ratio of metal stearate A to stearate amide in the above-described coating amount relationship, preferably 1:0.03 to 1:1.5, more preferably 1:0.05 to 1:1.5, and even more preferably 1:0.1 to 1:1.5. By satisfying this ratio, the fluidity of the foamed resin particles can be more sufficiently improved, and the feel of the final product, the cushioning material, can be made better.

[0028] (Antistatic agent) The foamed resin particles of the present invention contain an antistatic agent to improve the electrostatic properties of the foamed particles produced using them. The amount of antistatic agent coating per 100 parts by mass of the resin particle body is 0.2 parts by mass or more and 0.8 parts by mass or less, and more preferably 0.3 parts by mass or more and 0.5 parts by mass or less.

[0029] The antistatic agent can be appropriately selected from antistatic agents that can be used to prevent the foam particles from becoming statically charged. Preferred examples include fatty acid monoglycerides such as stearic acid monoglyceride, palmitic acid monoglyceride, and lauric acid monoglyceride, as well as hydroxyamine and polyethylene glycol.

[0030] In particular, in order to exhibit a more desirable antistatic effect in the present invention, it is preferable that the antistatic agent contains monoglyceride stearate and hydroxylamine, and it is more preferable that the mass ratio of monoglyceride stearate to hydroxylamine is 1:1.5 to 1:10, even more preferable that it is 1:1.5 to 1:8, and particularly preferable that it is 1:1.5 to 1:5.

[0031] [Any materials] The foamed resin particles of the present invention may further contain or be coated with any material. The above-mentioned material can be appropriately selected without departing from the spirit of the present invention, but for example, the resin particle body may contain polymers other than the polystyrene resin that is the base resin, as long as it does not hinder the intended purpose of the present invention. Other polymers include thermoplastic resins such as polyolefin resins, polyester resins, and polyamide resins, as well as thermoplastic elastomers such as styrene elastomers and olefin elastomers. When other polymers are contained in the resin particle body in addition to the polystyrene resin which is the base resin, the content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of polystyrene resin.

[0032] The bulk density of the foamed resin particles is preferably 16 to 50 kg / m³. 3 A more comfortable 20-35 kg / m 3 That is the case.

[0033] The resin particle body may contain conventionally known additives such as bubble regulators, plasticizers, antibacterial agents, and flame retardants in the base resin. Examples of foam regulators include polyethylene wax, talc, silica, ethylene bisstearylamide, methyl methacrylate copolymers, and silicones. Examples of plasticizers include liquid paraffin, glycerin diacetomolaurate, glycerin tristearate, di-2-ethylhexyl phthalate, and di-2-ethylhexyl adipate. Examples of antimicrobial agents include organic antimicrobial agents such as 3-iodo-2-propynylbutylcarbamate (IPBC), thiabendazole (TBZ), carbendazim (BCM), and chlorothalonil (TPN), as well as inorganic antimicrobial agents such as silver-based, copper-based, and titanium dioxide-based agents. Examples of flame retardants include organic flame retardants such as brominated flame retardants and phosphorus-based flame retardants, and inorganic flame retardants such as aluminum hydroxide, magnesium hydroxide, and antimony trioxide. Furthermore, the resin particles themselves may also contain colorants such as pigments and dyes.

[0034] The coating agent may include other coating components in addition to metal stearate A, stearate amide, and an antistatic agent, as long as they do not hinder the intended purpose of the present invention. Other coating components include conventionally known coating components such as silicone oil and higher fatty acid esters. Among these, it is preferable that the coating agent contains dimethylpolysiloxane because it can effectively suppress the detachment of metal stearate A, stearate amide, and antistatic agents from the resin particle body. The amount of dimethylpolysiloxane coating is preferably 0.01 parts by mass or more and 1.0 parts by mass or less, more preferably 0.03 parts by mass or more and 0.08 parts by mass or less, per 100 parts by mass of the resin particle body. Examples of commercially available dimethylpolysiloxane include, but are not limited to, silicone oil (KF96) manufactured by Shin-Etsu Chemical Co., Ltd. Furthermore, the coating agent may also contain other fatty acid metal salts other than stearate metal salt A, and other fatty acid amides other than stearate amide. Other examples of fatty acid metal salts include metal stearate salts such as barium stearate, aluminum stearate, and lithium stearate, and metal laurate salts such as zinc laurate and barium laurate, which are higher fatty acid metal salts that are metal salts of fatty acids with 12 to 24 carbon atoms. These fatty acid metal salts may be used alone or in combination of two or more fatty acid metal salts. Other examples of fatty acid amides include compounds such as stearate amide and N-stearyl stearate amide. The content of other fatty acid metal salts in the coating agent is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, per 100 parts by mass of stearate metal salt A. The content of other fatty acid amides is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, per 100 parts by mass of stearate amide.

[0035] (Foaming agent content in foamed resin particles) The foamed resin particles are dissolved in dimethylformamide (hereinafter referred to as DMF) to obtain a solution. The solution is subjected to gas chromatography analysis to measure the content of each foaming agent in the foamed resin particles. The quantitative determination of foaming agents by gas chromatography can be performed using the following procedure. First, approximately 5 g of cyclopentanol is accurately weighed to three decimal places and placed in a 100 mL volumetric flask. DMF is then added to make a total volume of 100 mL. The DMF solution thus obtained is further diluted 100-fold with DMF to prepare the internal standard solution. Next, approximately 1 g of foaming resin particles to be measured is accurately weighed to three decimal places. The accurately weighed foaming styrene resin particles are dissolved in approximately 18 mL of DMF to prepare a dissolution. 2 mL of the internal standard solution is accurately weighed using a volumetric pipette and added to the above dissolution to prepare the sample solution. 1 μL of this sample solution is introduced into a gas chromatography analyzer using a microsyringe to obtain a chromatogram. The peak areas of each foaming agent component and the internal standard substance are determined from the obtained chromatogram, and the concentration of each foaming agent contained in the foaming resin particles is determined using the following formula (1). [Mathematics 1] Concentration (mass%) of each foaming agent = [(Wi / 10000)×2]×[An / Ai]×Fn÷Ws×100···(1) The meanings of the symbols in equation (1) above are as follows: Wi: Mass (g) of cyclopentanol in internal standard solution Ws: Mass (g) of foamed resin particles dissolved in DMF An: Peak area of ​​each foaming agent component calculated from the chromatogram Ai: Peak area of ​​internal standard substance calculated from chromatogram Fn: Correction coefficient for each foaming agent component obtained from a pre-prepared calibration curve.

[0036] (Bulk density of foamed particles) Bulk density of foamed particles (kg / m³) 3 The process involves filling a graduated cylinder with foam particles and stabilizing the filling height of the foam particles at the 1L mark. Next, the mass (in g) of the foam particles in the graduated cylinder is measured. The mass of foam particles per 1L of bulk volume (in g / L) obtained in this way is then converted to determine the bulk density (in kg / m³). 3 It is possible to calculate ).

[0037] (Feel) A stretchable, bag-shaped cushion material (110cm x 125cm x 150cm) made of polyester fibers is filled with 2.2L of foamed particles to create a rectangular cushion material. This cushion material is placed on a test table, and panelists can feel its texture by pressing their palms downwards from the top surface. The texture can then be evaluated according to predetermined evaluation criteria.

[0038] [Method for manufacturing foamed resin particles] The method for producing the foamed resin particles of the present invention is not particularly limited, but for example, the foamed resin particles of the present invention can be produced by a turbidity polymerization method, similar to that used for general foamed styrene-based resin particles. More specifically, pre-foamed resin particles are obtained by placing a dispersion medium such as water, a resin material such as styrene monomer, a dispersant, a polymerization initiator, a foam regulator, etc., into an autoclave (sealed container) equipped with a stirring device, stirring, and carrying out turbid polymerization while supplying a foaming agent at appropriate timings. These pre-foamed resin particles are then dried and classified to obtain pre-foamed resin particles with a desired average particle size. Finally, foamed polystyrene resin particles are produced by coating the pre-foamed resin particles with a coating agent. The method of coating with the coating agent is not particularly limited, but for example, the resin particles and each component constituting the coating agent can be supplied to a mixer and mixed by stirring.

[0039] Examples of the above-mentioned dispersion medium include aqueous dispersion media such as water and deionized water. Examples of the above-mentioned dispersants include calcium phosphate such as tricalcium phosphate, disodium hydrogen phosphate, potassium persulfate, and sodium alkyldiphenyl ether disulfonate. Examples of polymerization initiators include benzoyl peroxide, t-butyl peroxy 2-ethylhexyl monocarbonate, lauryl peroxide, and t-butyl peroxybenzoate. Each component used in the turbid polymerization can be used individually or in combination. Furthermore, the components are not limited to the examples given above. At least some of these components may be contained in the manufactured foamed resin particles.

[0040] [Method for producing foamed particles] As described above, the foamed resin particles are fed into a foaming machine and heated by supplying a heating medium such as steam, causing the foamed resin particles to foam and obtain polystyrene-based foamed resin particles. As described above, the cushioning material is manufactured by filling the polystyrene foam particles into a bag using an air filling machine or the like. [Examples]

[0041] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the table, butane, which is a foaming agent, is denoted as C4, pentane as C5, and cyclohexane as CH. Magnesium stearate is denoted as MgSt, zinc stearate as ZnSt, calcium stearate as CaSt, stearate amide as SA, erucate amide as EA, stearate monoglyceride as GMS, and hydroxylamine as HA. In the table, the amount of each composition for the coating agent is shown as the amount (parts by mass) per 100 parts by mass of the resin particle body. <Example 1> First, 300 kg of deionized water, 1.39 kg of tricalcium phosphate, 0.08 kg of disodium hydrogen phosphate, 3.5 g of potassium persulfate, and 1.5 g of sodium alkyldiphenyl ether disulfonate (Perex SSH, manufactured by Kao Corporation) were added to a 760 L autoclave (sealed container) equipped with a stirring device. Next, while stirring the contents of the autoclave, 0.25 kg of foam regulator (polyethylene wax 1000, manufactured by Toyo Chem Co., Ltd.), 5 kg of cyclohexane as a foaming agent, and 252 kg of polymerization initiator and styrene were added to the autoclave. Furthermore, 0.94 kg of benzoyl peroxide (NOF Corporation's "NIPER® BW") and 0.54 kg of t-butyl peroxy 2-ethylhexyl monocarbonate (NOF Corporation's "Perbutyl® E") were used in combination as polymerization initiators. The contents of the autoclave were stirred at room temperature for 5 minutes, and then the temperature inside the autoclave was raised to 90°C over 30 minutes. After the temperature inside the autoclave reached 90°C, this temperature was maintained for 330 minutes (first half of the initial polymerization step). Next, the temperature inside the autoclave was heated to 96°C over 25 minutes and maintained for 52 minutes (second half of the initial polymerization step). Next, the temperature inside the autoclave was raised to 120°C over 96 minutes and maintained for 200 minutes (secondary polymerization step). After that, the temperature inside the autoclave was cooled to 25°C over 140 minutes. Through these steps, the styrene inside the autoclave was polymerized. Furthermore, a blowing agent was supplied into the autoclave during the first half of the preceding polymerization process. Specifically, the supply of the blowing agent into the autoclave began 364 minutes after the temperature inside the autoclave reached 90°C, and ended 60 minutes later. As described above, 7.6 kg of pentane (100% isopentane) and 7.6 kg of butane (a mixture of approximately 70% by mass of normal butane and approximately 30% by mass of isobutane) were used in combination as the blowing agent supplied during the first half of the preceding polymerization process.

[0042] After cooling in the autoclave was complete, the pre-foamed resin particles containing the foaming agent were removed from the autoclave. The pre-foamed resin particles were dehydrated and washed using a centrifuge, and then the moisture adhering to the surface of the pre-foamed resin particles was removed using an air-flow dryer. The dried pre-foamed resin particles were then classified to obtain pre-foamed resin particles with an average particle diameter of 0.4 mm. The average particle diameter of the pre-foamed resin particles is equal to the average particle diameter of the main particle body. Next, the surface of the pre-foamed resin particles obtained as described above was coated with a coating agent. Specifically, in a container containing the dried pre-foamed resin particles, 0.1 parts by mass of zinc stearate (Zn-St, manufactured by Nitto Chemical Industries, Ltd.), 0.2 parts by mass of magnesium stearate (Mg-St, manufactured by Nitto Chemical Industries, Ltd.), 0.1 parts by mass of glycerin monostearate (Rikemar S-100P, manufactured by Riken Vitamin Co., Ltd.), 0.35 parts by mass of hydroxyalkylamine (Antista 80FS, manufactured by Tanaka Chemical Research Institute Co., Ltd.), 0.05 parts by mass of stearate amide (Fatty Acid Amid S, manufactured by Kao Corporation), and 0.05 parts by mass of dimethylpolysiloxane (KF-96-100CS, manufactured by Shin-Etsu Chemical Co., Ltd.) were added per 100 parts by mass of the resin particle body, and the mixture was stirred and mixed to coat the surface of the resin particle body, thereby obtaining foamed resin particles. This was designated as Example 1.

[0043] [Production of foamed particles] As described above, the foamed resin particles obtained in Example 1 were placed into a pressurized foaming machine (DYHL500U, manufactured by Daisen Kogyo Co., Ltd.), and steam was supplied into the pressurized foaming machine. This caused the foamed resin particles to foam, and foamed particles were obtained.

[0044] (Examples 2-16) Examples 2 to 16 were produced using the same method as in Example 1, except that the contents shown in Table 1 or Table 2 were changed from those in Example 1. Furthermore, foamed resin particles were produced using the foamed resin particles of Examples 2 to 16 using the same method as in which foamed resin particles were produced using the foamed resin particles of Example 1.

[0045] (Comparative Examples 1-6) Comparative Examples 1 to 6 were produced using the same method as in Example 1, except that the changes shown in Table 3 were made compared to Example 1. Furthermore, foamed resin particles were produced using the foamed resin particles of Comparative Examples 1 to 6 using the same method as in Example 1. In Comparative Example 1, the calcium stearate used was "Ca-St" manufactured by Nitto Chemical Industries, Ltd., and in Comparative Example 5, the erucic acid amide used was "Fatty Acid Amid E" manufactured by Kao Corporation.

[0046] The foamed resin particles of the examples and comparative examples obtained as described above were measured or evaluated as follows. The results are shown in Tables 1 to 3. In the evaluations shown below, evaluations A and B were determined to be practical.

[0047] (Average particle size of foamed resin particles) Using a particle size distribution analyzer (manufactured by Nikkiso Co., Ltd., product name: Millitrack JPA), the cumulative 63% diameter (d63) of the foamed resin particles, calculated based on the volume-based particle size distribution, was measured and defined as the average particle diameter.

[0048] (Volatile content of foamed resin particles) Approximately 1 g of foamed resin particles was prepared and weighed to four decimal places to determine the pre-heating mass (W1). After weighing, the foamed resin particles were dried in a hot air dryer set to 120°C for 4 hours. After the dried foamed resin particles were cooled to room temperature, they were weighed to determine the post-heating mass (W2). The total volatile content was then calculated from the mass change rate before and after heating, as shown in equation (2) below. Next, the volatile component content was determined by subtracting the moisture content of the foamed resin particles before heating from the total volatile content, as shown in equation (3) below. For this measurement, five precisely weighed samples were prepared, and the procedure was performed on each sample. The arithmetic mean of these measured values ​​was taken as the volatile content of the foamed resin particles. The method for measuring the moisture content will be described later. [Math 2] Total volatile content (mass%) = [W1(g) - W2(g)] ÷ W1(g) × 100 ... (2) [Math 3] Volatile content (mass%) = Total volatile content (mass%) - Water content (mass%) ... (3)

[0049] (Moisture content of foamed resin particles) The moisture content of foamed resin particles was measured using a Karl Fischer moisture meter. Specifically, approximately 0.28 g of foamed resin particles was prepared, accurately weighed to four decimal places, and used as the sample. The sample was heated to 160°C using a moisture vaporizer to vaporize the moisture in the sample, and the vaporized moisture was then introduced into a Karl Fischer moisture meter, where the moisture content of the sample was measured by coulometric titration. For this measurement, five accurately weighed samples were prepared, and the procedure was performed on each sample. The arithmetic mean of these measured values ​​was taken as the moisture content of the foamed resin particles. A "CHK-501" manufactured by Kyoto Electronics Manufacturing Co., Ltd. was used as the moisture vaporizer. A "MKC-610" manufactured by Kyoto Electronics Manufacturing Co., Ltd. was used as the Karl Fischer moisture meter.

[0050] (Foaming agent content in foamed resin particles) Following the method for measuring the foaming agent content of foamed resin particles described above, the foaming agent content of the foamed resin particles in the examples and comparative examples was measured. Specifically, five precisely weighed samples were prepared, and the foaming agent content was measured for each sample. The arithmetic mean of these measurements was taken as the foaming agent content of the foamed resin particles. The detailed analytical conditions in the gas chromatograph were as follows. Analytical instrument: Shimadzu Corporation, Gas Chromatograph GC-6AM Detector: FID (Flame Ionization Detector) Column material: Glass column with an inner diameter of 3 mm and a length of 5000 mm. Column packing material: [Liquid phase name] FFAP (free fatty acids), [Liquid phase impregnation rate] 10% by mass, [Carrier name] Chomasorb W diatomaceous earth for gas chromatography, [Carrier particle size] 60 / 80 mesh, [Carrier treatment method] AW-DMCS (water washing, calcination, acid treatment, silane treatment), [Packing volume] 90 mL Inlet temperature: 250℃ Column temperature: 120℃ Detection unit temperature: 250℃ Carrier gas: N2, flow rate 40 ml / min

[0051] (R-SM content of foamed resin particles) The content of unreacted styrene (R-SM) in foamed resin particles was measured using a headspace gas chromatograph-mass spectrometer. First, three standard solutions were prepared so that the styrene concentration in DMF was 5 ppm, 50 ppm, or 500 ppm by mass. 0.2 g of each standard solution was accurately weighed and placed in a 20 ml vial, and then 1 ml of DMF was added and sealed. The gas phase of the vial was measured using a gas chromatograph-mass spectrometer, and a calibration curve was created from the obtained chromatogram. Next, 0.2 g of foamed resin particles was accurately weighed and placed in a 20 ml vial with 1 ml of DMF and sealed. This vial was kept at room temperature for 1 day to completely dissolve the foamed resin particles in the DMF. After that, the gas phase of the vial was measured using a gas chromatograph-mass spectrometer, and the content of unreacted styrene (ppm by mass) in the foamed resin particles was determined from the obtained chromatogram and the previously prepared calibration curve. For this measurement, five of the above samples were prepared, and the procedure was performed on each sample. The arithmetic mean of these measurements was taken as the R-SM amount of the foamed resin particles. The measurement conditions for gas chromatography-mass spectrometry were as follows. Gas chromatograph-mass spectrometer: Shimadzu Corporation GCMS-QP2020 Headspace sampler: Shimadzu Corporation HS-20 Capillary column: Stabilwax, manufactured by GL Sciences Co., Ltd., inner diameter 0.32 mm, length 30 m Headspace sampler heating conditions: 90°C, 1 hour Column temperature: 50°C x 2 mins → (heating rate: 10°C / min) → 90°C → (heating rate: 5°C / min) → 120°C → (heating rate: 20°C / min) → 230°C x 2 mins Ion source temperature: 200℃ Carrier gas: Helium, Column flow rate: 2 ml / min Split ratio: 1 / 10

[0052] (Weight-average molecular weight of foamed resin particles) The weight-average molecular weight of foamed resin particles was measured using gel permeation chromatography (GPC) with polystyrene as the standard substance. A Tosoh Corporation HLC-8320GPC EcoSEC was used to obtain the chromatograms. Each foamed resin particle of the sample was dissolved in tetrahydrofuran (THF) to prepare a 0.1% by mass sample solution. Then, under the following conditions, the samples were separated by molecular weight using gel permeation chromatography (GPC) to obtain chromatograms. The retention time in the chromatogram was then converted to molecular weight using a calibration curve created with standard polystyrene to obtain a differential molecular weight distribution curve. The weight-average molecular weight (Mw) of the sample was calculated from this differential molecular weight distribution curve. Columns: One TSKguardcolumn SuperH-H and two TSK-GEL SuperHM-H columns were connected in series. Eluent: Tetrahydrofuran Tetrahydrofuran flow rate: 0.6 ml / min

[0053] (Evaluation of the fluidity of foamed resin particles) The foamed resin particles coated with a coating agent were filled to the brim into a 100 ml disposable cup, and the cup was placed in a constant temperature and humidity chamber at 60°C and 60% humidity for 1 hour. After that, the disposable cup was removed from the constant temperature and humidity chamber, and its opening was covered with a measuring card with concentric circular markings. The cup was slowly moved up and down so that the opening faced downwards, and placed on the top surface of the test stand with the bottom surface of the card in contact with it. At this time, the cup was positioned so that the center of the opening coincided with the center of the concentric circular markings. With the cup still on the test stand, the disposable cup was slowly lifted vertically upwards, and the diameter of the foamed resin particle group spread out on the measuring card (the point where the distance from the outer edge to the outer edge of the foamed resin particle group is largest, passing through the center of the markings) was measured. Based on the diameter of the foamed resin particle group spread out on the card, the fluidity of the foamed resin particles was evaluated according to the following criteria. A: The diameter was 85 mm or more. B: The diameter was 75 mm or more and less than 85 mm. C: Diameter less than 75 mm or clumps were visually observed in the foamed resin particle group.

[0054] (Evaluation of blocking occurrence in foamed resin particles) Approximately 4200g of foamed particles immediately after being removed from the foaming machine were sieved through a 2.8mm square mesh. The mass of the foamed particles remaining on the mesh was measured, and the ratio of the masses of the foamed particles remaining on the mesh was calculated. Based on this ratio, the occurrence of blocking of the foamed resin particles was evaluated according to the following criteria. A: The ratio was less than 0.1%. B: The ratio was between 0.1% and 0.2%. C: The ratio was 0.2% or higher.

[0055] (Evaluation of foaming properties of foamed resin particles) In a foaming chamber, foamable resin particles were heated for 270 seconds using steam at a gauge pressure of 3 kPa (G) to produce foamed resin particles. After air-drying these foamed particles overnight, the bulk density of each foamed particle was measured (unit: kg / m³) in accordance with the method described above for measuring the bulk density of foamed particles. 3 The foaming properties of foamed resin particles were evaluated based on the bulk density of the foamed particles when foamed under certain conditions, according to the following criteria. A: The bulk density was between 12 g / L and 15 g / L. B: The bulk density was between 15 g / L and 30 g / L. C: The bulk density was 30 g / L or higher.

[0056] The foamed resin particles produced by foaming the foamed resin particles of each example and comparative example were measured or evaluated as follows. The results are shown in Tables 1 to 3. In the evaluations shown below, evaluations A and B were determined to be practical.

[0057] (Measurement of bulk density of foamed particles) Following the measurement of the bulk density of the foamed particles described above, the bulk density of each foamed particle (unit: kg / m³) was measured. 3 ) was sought.

[0058] (Evaluation of the fluidity of foamed particles) Aside from using foamed particles instead of foamed resin particles, the fluidity of each foamed particle was checked in accordance with the method for confirming the fluidity of foamed resin particles described above, the diameter of the foamed particle group spread on the base was measured, and it was evaluated according to the following criteria. A: The diameter was 85 mm or more. C: Diameter less than 85 mm or clumps were visually observed in the foamed particle group.

[0059] (Measurement of the collapse rate of foamed particles) A foaming particle with a bulk volume of 330 ml is enclosed in an inner diameter of 7.8 cm with a volume of 61.6 cm³. 3The foamed particles were placed in a cylindrical metal container. Using a metal disc-shaped jig with a diameter of 7.7 cm, the foamed particles were compressed from the top at a speed of 10 m / min until the compression load reached 650 N, and this was repeated 100 times. After the repeated compression was completed, the bulk volume of the foamed particles in the container was measured, and the collapse rate (volume reduction rate) was calculated using the following formula (4). The test machine used for the repeated compression operation was an Autograph AG-X plus 100kN manufactured by Shimadzu Corporation. [Math 4] Sagging rate = (Volume before the test - Volume immediately after the test) ÷ Volume before the test × 100 ... (4)

[0060] (Evaluation of the charge amount and chargeability of foamed particles) The foamed particles were placed in a constant temperature and humidity chamber at 23°C and 50% humidity and cured for 24 hours. The bulk volume of the cured foamed particles (330 ml) was then measured in a container with an inner diameter of 7.8 cm and a volume of 61.6 cm³. 3 The foam particles were placed in a cylindrical metal container. During this process, a mascot static eliminator (manual static eliminator) was used to eliminate static electricity while the foam particles were placed inside. Preparations were made so that the initial charge level was 0V at a position 10mm from the surface of the foam particles. Then, using a metal disc-shaped jig with a diameter of 7.7cm, the foam particles were compressed from the top side at a compression speed of 60mm / min until the compression load reached 650N, and this was repeated 100 times. 30 seconds after the end of the repeated compression, the voltage [V] was measured at a position 25mm above the top surface of the foam particles inside the container. The test machine used for repeated compression was an Autograph AG-X plus 100kN manufactured by Shimadzu Corporation. The voltage withstand test instrument used was a digital low-potential meter KSD-3000 manufactured by Kasuga Electric Co., Ltd. Based on the charge levels measured as described above, the electrostatic properties of the foam particles were evaluated as follows. A: The charge was between -10V and +10V. B: The charge level was between -25V and -10V. C: The charge level was less than -25V.

[0061] (R-SM content of foamed particles) The R-SM amount (mass ppm) of the expanded particles was measured in the same manner as the measurement of the R-SM amount of the expandable resin particles described above, except that the sample used was changed from expandable resin particles to expanded particles.

[0062] (VOC emission amount of expanded particles) First, the expanded particles were placed in a thermo-hygrostat at a temperature of 23°C and a humidity of 50% and conditioned for 2 days. Following JIS A 1901:2015, the conditioned expanded particles were placed on the inner bottom surface of a 20 L small stainless steel chamber so that the surface area was 320 cm 2 , and the amount of VOC emitted from the expanded particles (μg / m 2 / m 3 ) was measured under the condition of a test load rate of 1.6 m 3 .

[0063] An elastic bag body (110 cm × 125 cm × 150 cm) made of polyester-based fibers was filled with 2.2 L of expanded particles by volume to produce a rectangular cushioning material. This was placed on a test bench, and panelists placed their palms on the upper surface of the cushioning material and pushed downward to confirm the feel, and the feel was evaluated according to the following evaluation criteria. The panelists were 10 people randomly selected, and when the total score of the evaluations of the 10 people was 27 points or more according to the following criteria, it was evaluated as "A", when the total score of the 10 people was 20 points or more and 26 points or less, it was evaluated as "B", and when the total score of the 10 people was 19 points or less, it was evaluated as "C" to evaluate the feel of the cushioning material. 3 points: High fluidity and a smooth feel. 2 points: Has fluidity, but sometimes has a rough feel. 1 point: Low fluidity and a rough feel.

[0064]

Table 1

[0065]

Table 2

[0066] [Table 3]

[0067] The present invention described above encompasses the following technical concepts. (1) Expandable polystyrene resin particles for cushioning material filling, comprising a resin particle body with a polystyrene resin as the base resin, a foaming agent contained in the resin particle body, and a coating agent covering the resin particle body, The average particle diameter of the resin particle body is 0.3 mm or more and 0.5 mm or less. The coating agent comprises metal stearate A, stearate amide, and an antistatic agent. The metal stearate salt A consists of 40% to 100% by mass of magnesium stearate and 0% to 60% by mass of zinc stearate (provided that the sum of both is 100% by mass). Expandable polystyrene resin particles for cushioning material, wherein the amount of coating of the metal stearate salt A is 0.1 parts by mass or more and less than 0.4 parts by mass per 100 parts by mass of the resin particle body, the amount of coating of the stearate amide is 0.01 parts by mass or more and 0.5 parts by mass or less, and the amount of coating of the antistatic agent is 0.2 parts by mass or more and 0.8 parts by mass or less. (2) The foamable polystyrene resin particles for cushioning material filling described in (1) above, wherein the amount of magnesium stearate coating per 100 parts by mass of the resin particle body is 0.1 parts by mass or more and less than 0.4 parts by mass, and the amount of zinc stearate coating is less than 0.2 parts by mass (however, including 0 parts by mass). (3) Expandable polystyrene resin particles for cushioning material filling as described in (1) or (2) above, wherein the metal stearate salt A consists of 60% by mass or more and 80% by mass or less of magnesium stearate and 20% by mass or more and 40% by mass or less of zinc stearate (provided that the sum of both is 100% by mass). (4) Expandable polystyrene resin particles for cushioning material filling according to any one of (1) to (3) above, wherein the mass ratio of the metal stearate salt A to the stearate amide is 1:0.05 to 1:1.5. (5) Expandable polystyrene resin particles for cushioning material filling according to any one of (1) to (4) above, wherein the antistatic agent comprises monoglyceride stearate and hydroxylamine, and the mass ratio of monoglyceride stearate to hydroxylamine is 1:1.5 to 1:10. (6) The foaming agent comprises butane, pentane, and cyclohexane, the total content of butane, pentane, and cyclohexane in the foamable polystyrene resin particles is 4% by mass or more and 8% by mass or less per 100% by mass of the foamable resin particles, and the mass ratio of the total of butane and pentane to cyclohexane is 1:0.1 to 1:0.5, as described in any of (1) to (5) above.

Claims

1. The expandable polystyrene-based resin particles for use as filling for cushioning material are composed of a resin particle body having a polystyrene-based resin as a base resin, a foaming agent contained in the resin particle body, and a coating agent coating the resin particle body, The average particle diameter of the resin particle body is 0.3 mm or more and 0.5 mm or less, the coating agent comprises a metal stearate A, stearic acid amide and an antistatic agent; The metal stearate A is composed of 40% by mass or more and 100% by mass or less of magnesium stearate and 0% by mass or more and 60% by mass or less of zinc stearate (the total of both is 100% by mass), Expandable polystyrene-based resin particles for filling cushioning material, in which the coating amount of the metal stearate A is 0.1 parts by mass or more and less than 0.4 parts by mass, the coating amount of the stearamide is 0.01 parts by mass or more and 0.5 parts by mass or less, and the coating amount of the antistatic agent is 0.2 parts by mass or more and 0.8 parts by mass or less, relative to 100 parts by mass of the resin particle body.

2. 2. The expandable polystyrene-based resin particles for filling cushioning material according to claim 1, wherein the amount of coating of the magnesium stearate is 0.1 parts by mass or more and less than 0.4 parts by mass, and the amount of coating of the zinc stearate is less than 0.2 parts by mass (including 0 parts by mass) relative to 100 parts by mass of the resin particle body.

3. 3. The expandable polystyrene-based resin particles for filling cushioning material according to claim 1 or 2, wherein the metal stearate A is composed of 60% by mass or more and 80% by mass or less of magnesium stearate and 20% by mass or more and 40% by mass or less of zinc stearate (the sum of the two being 100% by mass).

4. 4. The expandable polystyrene-based resin particles for filling a cushioning material according to claim 1, wherein a mass ratio of said metal stearate A to said stearamide is 1:0.05 to 1:1.

5.

5. The expandable polystyrene-based resin particles for filling a cushioning material according to any one of claims 1 to 4, wherein the antistatic agent comprises stearic acid monoglyceride and hydroxylamine, and the mass ratio of the stearic acid monoglyceride to the hydroxylamine is 1:1.5 to 1:

10.

6. The expandable polystyrene-based resin particles for filling a cushioning material according to any one of claims 1 to 5, wherein the foaming agent contains butane, pentane and cyclohexane, the total content of butane, pentane and cyclohexane in the expandable polystyrene-based resin particles is 4% by mass or more and 8% by mass or less relative to 100% by mass of the expandable resin particles, and the mass ratio of the total of butane and pentane to cyclohexane is 1:0.1 to 1:0.5.